THE BATTLE AT PANTINO IN 1168 AND THE UNITY OF THE SERBIAN STATE (Heritage, 2020)
The battle near the village of Pantino represents a turning point in the development of the Serbian medieval state. It cannot be stated with certainty when it took place, although it is asserted with great probability it happened in 1168.  In this battle Stefan Nemanja defeated his brothers assisted with Byzantine’s army, soldiers of fortune Turks, Frugus (Franks) and other peoples and finally ascended the throne of the great prefect of Serbia.  The battle near Pantino is important due to the fact that it, directly or indirectly, found the place with great Byzantine’s writers such as Joannes Kinamos and Niketas Choniates and with Nemanja’s hagiography writers Stefan the First Crowned ad Domentian. Besides the above mentioned, data of this battle are fragmentized and modest and they do not give the opportunity to describe it more thoroughly.         It was noticed a long time ago the battle represented a turning point for further development of Serbian medieval state, not only in political, military and organizational way but in symbolic as well.  After the battle in which Stefan Nemanja defeated his brothers, the situation in Serbia became more clearer and calmer. The changes on the throne stopped happening, which after Uroš II had been so frequent.  In this battle Stefan Nemanja, from the  favorite of the basileus Manuel, who  had just given him the area of Dubočica, and the title of „tsar’s dream“, became his opponent.  Nemanja is appearing in it as the fighter for the state unity, contrary to his brothers whom supported by Byzantine, are struggling for sharing parts division and preservation of the previous state in which basileos had decisively influenced the great prefect choice.  By his victory he achieved that the state became unique, and he came to power against the will of the basileus Manuel. The victory in the battle near Pantino reflected on the fundraising activity of Stefan Nemanja.  Symbolic of the built monasteries of St. George in Ras and Studenica speaks on military victory over the enemies and on the established state unity.
Keywords: Stefan Nemanja, the Battle near Pantino, Manuel Komnenus, Serbia, Byzantine, Unity of the state